Can magnetopause reconnection drive Saturn's magnetosphere?. Issue 6 (27th March 2014) - Masters, A.; Fujimoto, M.; Hasegawa, H.; Russell, C. T.; Coates, A. J.; Dougherty, M. K.
Abstract While solar wind‐driven compression of Saturn's magnetosphere is an important trigger of magnetospheric dynamics, the importance of magnetopause reconnection has been the subject of debate. Here we use Cassini observations at Saturn's magnetopause to address this open issue. Measured conditions at the boundary suggest a typical reconnection electric field strength of order 0.01 mV m−1. Although the strongest reconnection electric fields correspond to a compressed magnetosphere, compressed conditions do not guarantee a relatively strong reconnection electric field at the magnetopause location sampled by the spacecraft. By considering northward Interplanetary Magnetic Field (IMF), we predict reconnection voltages (open magnetic flux production rates) for the strongest driving of Saturn's magnetosphere by magnetopause reconnection. The typical northward IMF reconnection voltage is less than 100 kV for a wide range of reconnection X line lengths. This suggests that magnetopause reconnection is not a major driver of dynamics in Saturn's magnetosphere, except possibly on rare occasions.